Urban Jamification: Gincanas as location-based mobile games in Brazil - de Souza e Silva, Adriana; Froes, Isabel (AoIR Selected Papers of Internet Research, 2013)
Gincanas are a traditional event in Brazilian culture where groups of people compete against each other by solving tasks. Recently, the Dutch Waag Society and the Brazilian Mobilefest developed the location-based game called Global Gincana, where players use their phones as interfaces to interact with the game space through solving location-based tasks about the countries’ history and culture. By exploring the history of Brazilian gincanas and how they have evolved through the spread and appropriation of mobile technologies, this article addresses two main research questions: (1) how mobility and the configuration of urban space influence the design and performance of location-based mobile games; and (2) how the urban and socio-economic context of developing countries, specifically Brazil, shape mobile technology appropriation and location-based mobile game design. We demonstrate that urban spaces can convey a multiplicity of performances, encompassing a vast arrange of applications, ranging from education and philanthropic to marketing oriented.